Phenolic compounds from Bidens pilosa methanolic fraction on induced gastric neoplasia in rats - Arroyo, Jorge (2007)
Objective: To determine the influence of both the ethanolic extract and the methanolic fraction containing phenolic and flavonoids compounds of Bidens pilosa L whole plant on gastric cancer induced in rats with N-nitroso-N-methylurea (NMU). Design: Experimental. Setting: Instituto de Investigaciones ClínicasBioterio, Facultad de Medicina UNMSM. Biologic material: Holtzmann male albino rats. Interventions: Following Ferraz de Souza et al., 2002, we had a normal control group, a group with NMU and NMU groups plus treatments with ethanolic extract and methanolic fraction at 300 mg/kg doses. For statistical significance we considered p<0,05. Main outcome measures: Progresion of gastric neoplasia induced in rats. Results: Indicate dysplasia and initial stages of carcinoma in the rats stomachs, which was less evident in the animals with treatment, being better the group that received the methanolic fraction. The marker of oxidative stress decreased in the groups that received treatment with the plant, being better the methanolic fraction. We observed less amount of micronuclei (genotoxicity) in the animals that received treatment. Conclusions: In experimental conditions the ethanolic extract and methanolic fraction delayed the advance of gastric cancer induced in rats.